Tom Gates: Dogzombies Rule (for Now...) - Liz Pichon (London : Scholastic Children's Books, 2017)
Here's my EXCELLENT PLAN to make DogZombies the BEST band in the WHOLE WIDE WORLD! How hard can it be? (Very.) Right now I'm going to: 1. Write more songs. (Not about teachers.) 2. Make a SPECTACULAR music video. (Easy.) 3. Get some sleep. (Tricky when you're being kept awake by LOUD NOISES.) 4. Annoy Delia. (Nothing to do with DOGZOMBIES but always FUN.)